Growth and Performance of Indian Fish and Fishery Products Exports - Radhakrishnan, K.; Tesfom, M. A.; Krishnan, M.; Infantina, J. Amali; Sivaraman, I. (Fishery Technology, 2018)
This study profiles the growth and instability of the Indian fish and fishery products export and its performance over the past five decades. The results show that growth rates of seafood exports has been increasing, though the instability increased. The possible reason for the growth and instability of Indian fish and fishery exports have also been discussed in this study.